计算(1-1/2-1/3-1/4-1/5)(1/2+1/3+1/4+1/5+1/6)-(1-1/2-1/3-1/4-1/
2个回答
设u=1/2+1/3+1/4+1/5,
v=1/2+1/3+1/4+1/5+1/6.
原式=(1-u)v-(1-v)u=v-u=1/6
相关问题
1.计算1/(1+√2)+1/(√2+√3)+1/(√3+√4)+1/(√4+√5)+1/(√5+√6)
计算:(1-1/2-1/3-1/4-1/5)乘以(1/2+1/3+1/4+1/5+1/6)-(1-1/2-1/3-1/4
计算2/1+(3/1+3/2)+(4/1+4/2+4/3)+(5/1+5/2+5/3+5/4)+.+(6/1+60/2+
计算:1/2+(1/3+2/3)+(1/4+2/4+3/4)+(1/5+2/5+3/5+4/5)+…+(1/60+2/6
(1/1+2)+(1/1+2+3)+(1/1+2+3+4)+(1/1+2+3+4+5)+.+(1/1+2+3+4+5+6
已知 1/2*3=1/2-1/3,1/3-1/4=1/12 计算1/3*4+1/4*5+1/5*6+1/6*7+1/7*
(1+2+3+4/1)+(1+2+3+4+5/1)+(1+2+3+4+5+6/1)+.+(1+2+3+4+.+99/1)
计算1/1*2+1/2*3+1/3*4+1/4*5+1/5*6+1/6*7的值
(2+1/3+1/4+1/5)×(1/3+1/4+1/5+1/6)—(2+1/3+1/4+1/5+1/6)×(1/3+1
(1+1/2+1/3+1/4+1/5)x(1/2+1/3+1/4+1/5+1/6)-(1+1/2+1/3+1/4+1/5